2018
DOI: 10.1007/s00441-018-2818-x
|View full text |Cite
|
Sign up to set email alerts
|

The accessory magnocellular neurosecretory system of the rostral human hypothalamus

Abstract: The morphology and neurophysin expression of the magnocellular accessory neuroendocrine system located in the rostral human hypothalamus is investigated in a series of brains obtained at autopsy. The hypothalami were fixed in formalin and embedded in paraffin, or after cryoprotection, frozen for cryostat sectioning. Paraffin sections were either stained with Luxol Fast blue or immunoreacted for neurophysin I or neurophysin II, the precursor molecule for oxytocin and vasopressin. Further, 50-μm-thick serial cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…In our immunohistochemical investigations of the accessory magnocellular neurosecretory system of the human hypothalamus (Møller et al, 2018), we found no correlation between the postmortem time and the immunoreactivity in our sections. An explanation for that several of our autopsy brains with long postmortem time has preserved protein, and mRNA might be due to the fact that the dead bodies in our study were kept cold in the morgue during most of the postmortem time, and after removal of the brains, these were immediate fixed by immersion in cold formalin.…”
Section: Studies Of the Plasma Levels Of Vasopressin In Schizophreniccontrasting
confidence: 73%
See 1 more Smart Citation
“…In our immunohistochemical investigations of the accessory magnocellular neurosecretory system of the human hypothalamus (Møller et al, 2018), we found no correlation between the postmortem time and the immunoreactivity in our sections. An explanation for that several of our autopsy brains with long postmortem time has preserved protein, and mRNA might be due to the fact that the dead bodies in our study were kept cold in the morgue during most of the postmortem time, and after removal of the brains, these were immediate fixed by immersion in cold formalin.…”
Section: Studies Of the Plasma Levels Of Vasopressin In Schizophreniccontrasting
confidence: 73%
“…The nona peptide, vasopressin, is a part of the hypothalamic–pituitary–adrenal axis. This hormone is located in magnocellular neurons in the human hypothalamic paraventricular nucleus of the hypothalamus (Møller et al, ; Saper, ) in which parvocellular neurons, containing corticotropin‐releasing hormone (CRH), also are located. Although the main function of vasopressin, also called the antidiuretic hormone (ADH), is the regulation of water re‐absorption in the kidney, via projections of axons to the posterior pituitary lobe and release of the hormone to the vascular system, vasopressin is also involved in regulation of cortisol from the suprarenal glands (Aguilera & Rabadan‐Diehl, ).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleus circularis (NC; also called accessory supraoptic nucleus in the rat in Bodian and Maren () was clearly present in the pig, disambiguating it from the VON (van Eerdenburg & Swaab, ). It is also present in rats (Price Peterson, ), hamsters (Ferris, Axelson, Martin, & Roberge, ), cats (Caverson et al, ), dogs (Laqueur, ), and was recently reported in the human hypothalamus (Møller et al, ) and has been linked to osmotic functions in rats (Wallace & Harrell, ) and flank marking in hamsters (Ferris et al, ). We were not able to detect any NC in the bovine hypothalamus.…”
Section: Discussionmentioning
confidence: 91%
“…Originally most authors found these cells to be accessory subnuclei to the PVN and the SON (Dellmann, ; Junge, ; Koikegami, ; Morton, ; Scharrer & Scharrer, ), based on various species. Other research groups chose to consider it a different entity (Braak & Braak, ; Gadamski & Lakomy, ; Szteyn et al, ; van Eerdenburg et al, ; Vierling, , ) while later, the concept of islands being part of a supraoptico‐paraventriculo‐hypohysal system emerged (Dierickx & Vandesande, ; Marani, ; Møller et al, ; Silverman & Zimmerman, ) following the human structure of these clusters. We subscribe to the argument of van Eerdenburg et al () in that the VON is obviously related to the PVN and SCN, because of its content of AVP and OXT and cell size, and is part of the hypothalamic magnocellular neurosecretory system although in the case of the pig and cattle at least, the organization into one distinct nucleus is striking (Figures and a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation